2014
DOI: 10.1161/circulationaha.113.007253
|View full text |Cite
|
Sign up to set email alerts
|

Troponin T and B-Type Natriuretic Peptide After On-Pump Cardiac Surgery

Abstract: Surgical risk stratification models, 1 including the European System for Cardiac Operative Risk Evaluation (EuroSCORE), 2,3 exclusively consider preoperative and intraoperative risk factors. Although useful for healthcare planning and for preoperative risk/benefit assessments, this view may prove fragmentary postoperatively, because it disregards perioperative myocardial ischemic events 4,5 or postoperative complications 6-8 despite their association with mortality. Therefore, there is a need for tools that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…(17) In that study, post-operative BNP had additional predictive value for 1-year mortality when combined with the logistic EuroSCORE. (17) In another study that included only valvular surgery patients, pre-operative BNP levels were found to be predictive of post-operative inotrope duration (OR=5.9, 95% CI 1.2, 29.68) and ventilation time (OR= 4.7, 95% CI 1.74,17.21). (20) BNP and NT-proBNP levels reflect cardiac filling pressures.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…(17) In that study, post-operative BNP had additional predictive value for 1-year mortality when combined with the logistic EuroSCORE. (17) In another study that included only valvular surgery patients, pre-operative BNP levels were found to be predictive of post-operative inotrope duration (OR=5.9, 95% CI 1.2, 29.68) and ventilation time (OR= 4.7, 95% CI 1.74,17.21). (20) BNP and NT-proBNP levels reflect cardiac filling pressures.…”
Section: Discussionmentioning
confidence: 87%
“…(16) A prospective cohort including 1,559 patients undergoing on-pump cardiac surgery reported that a post-operative (day 1 and 2) BNP value >790 ng/L was associated with an adjusted HR for mortality of 2.44 (95% CI 1.65–3.62). (17) In that study, post-operative BNP had additional predictive value for 1-year mortality when combined with the logistic EuroSCORE. (17) In another study that included only valvular surgery patients, pre-operative BNP levels were found to be predictive of post-operative inotrope duration (OR=5.9, 95% CI 1.2, 29.68) and ventilation time (OR= 4.7, 95% CI 1.74,17.21).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Many studies have demonstrated the usefulness of the serum BNP concentration in the diagnosis of HF ( 2 - 5 ). Furthermore, several studies have reported that the serum BNP concentration has prognostic value in HF patients ( 6 - 8 ); thus, BNP is considered to be the gold standard for predicting the outcome of HF.…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic factors in cardiac surgery are troponin and BNP. 16,17 The survival analysis in the present study showed that lnBNP, smoking, emergency operation, and PNI were prognostic factors in patients undergoing cardiovascular surgery. Smoking and an emergency operation have been reported as risk factors for surgery 1820 and regulated prognostic factors; these results are consistent with the findings of our study, in which they were also prognostic factors.…”
Section: Discussionmentioning
confidence: 51%